Estratégia de controle adaptiva para estabilização de um quadricóptero na presença de variação de massa - Souza, Rafael Monteiro Jorge Alves de (2016)
This work aims the development of an adaptive control strategy on stabilization and path tracking tasks of a quadrotor vehicle. The quadrotor is defined as a Vertical Take Off and Landing (VTOL) aircraft and it has emerged, in the second half of the 2000s as a promising platform for use in many purposes, mainly due to its mechanical simplicity, high payload and robustness. Therefore, this aircraft has been widely exploited on this area, which researches has focusing, as this work , to propose numerical methods in order to improve the autonomy and reliability in practical use of these vehicles. The helicopter model of the helicopter was obtained from the Euler-Lagrange formalism, considering it as a rigid body, symmetrical and taking the origin of the coordinate system coincides with the center of gravity of the vehicle. In order to obtain a more accurate model compared to the actual flight situation, the Gyro effect on body and propellers was considered. From the perspective of control engineering, it is considered an underactuated system which has 4 inputs (associated with four angular velocities of the rotors) and six state variables (corresponding to generalized coordinates of Lagrangian mechanics) A simulator was developed on Simulink® platform evaluated from the model obtained as a way to check on the effectiveness of the proposed control strategies. Initially, it was implemented a classic PID controller in order to stabilize the, and then the results were compared to the data present in the literature in order to ensure the reliability of the routine implemented. Lastly, an adaptive PID control strategy was proposed from the implementation of heuristic programming based on genetic algorithms to identify optimal gains controllers to the coordinates z , x and y subsystems. The results indicated a significant performance gain of the adaptive method over the classic PID for stabilization and path tracking tasks of a quadrirrotor vehicle in the presence of mass variation.